Barriers and facilitators in the junior-to-senior transition in male football: a scoping review - Tomás, J.; Araújo, D.; Martinho, D.; Ribeiro, J.; Sousa, H.; Field, A.; Sarmento, H. (Sports, 2025)
Background: Despite many young players showing strong potential, only a small fraction succeeds in the critical transition from youth to elite senior football. This scoping review synthesizes research on the junior-to-senior transition in men`s football, identifying main topics related with barriers and facilitators in the transition.